Return-Volatility Spillovers between Malaysian Islamic and Conventional Equity Markets - Matiur Rahman; Lonnie Turpin; Muhammad Mustafa (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2022)
Introduction: Financial volatility spillover effects have also been of keen interest to economic policymakers. The viability of financial institutions and the smooth functioning of financial markets may be disrupted by increasing financial volatility spillover effects. A better understanding across markets is essential for policymakers, investors, and consumers. Purpose: This paper explores the issue of return-volatility spillovers in a bivariate context between the Malaysian Islamic equity market, Dow-Jones Islamic Market, Malaysian Conventional equity market, and overall US stock market creating four different pairs. Methodology: GARCH-M models are estimated using daily data from January 2007 through June 2019. Findings: In all four cases, there is evidence of weak returns and volatility spillovers from one market to another. They imply relative tranquility between markets, as considered at a time. Islamic equity markets do not seem distinct from conventional equity markets from investors’ perspectives. Investors may thus prefer to invest in both Islamic and conventional equities for portfolio diversification.